Imagining the 'Enemy': adversarial roles in Rabindranath Tagore's short stories - Quayum, Mohammad Abdul (2016)
This essay investigates Rabindranath Tagore’s portrayal of antagonists or adversarial characters in a select body of his short stories, and argues that his perception of the antagonist is rooted in the influences of the Upanishads and the Bhagavad-Gita on his literary sensibility. Cut off from the paramatman and their antarkarana, his antagonists live in adviya and in rajasic or tamasic states